Legal review on the fixed-term contract workers: a comparative study between Malaysia and the United Kingdom / Sarilnezam Salleh … [et al.] - Salleh, Sarilnezam; Manas, Nur Hidayahtul Nabihah; Shahrul Nizam, Shahrul Amin; Othaman, Siti Salwa (2013)
This research focus on the fixed-term contract workers which is a type of employment whereby the workers is employed for a specific period of time or until a certain task is completed. The objective of this research is to examine the rights and protection provided for the fixed-term contract workers in the Employment Act 1955 and to set up a legal bench mark by comparing the employment law in the United Kingdom and in Malaysia. The first phase of this study involves general overview of the research on the historical perspective, and the controversy arises from the recent amendment of the Employment Act 1955. The second phase of this study describes the problems regarding fixed-term contract employment in Malaysia. The third phaseillustrates the development of employment law in United Kingdom. This research shows that fixed-term worker in Malaysia suffers from lack of protection and statutory rights due to the absence of specific legislation to regulate this type of employment. By identifying the cause of the problems, we will be able to produce solution as to eliminate the problem. This will put a stop to the employer from exploiting the fixed-term workers.